2014
DOI: 10.1021/jp411715n
|View full text |Cite
|
Sign up to set email alerts
|

D-π-A Porphyrin Employing an Indoline Donor Group for High Efficiency Dye-Sensitized Solar Cells

Abstract: Dye-sensitized solar cell (DSC) devices were fabricated using a novel donor-(π bridge)-acceptor (D-π-A) porphyrin sensitizer, VC-70, in which an indoline is linked directly to the porphyrin core and functions as the donor group. The best efficiencies of VC-70 and reference YD2-o-C8 devices were found to be 7.31 and 7.60%, respectively, and AMG 1.5 illumination and device properties were fully characterized using transient absorption, charge extraction, and transient photovoltage techniques. A notable effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 22 publications
0
27
1
Order By: Relevance
“…Finally, indoline-conjugated units have been considered, producing DSSCs with improved photocollection over a wide range of wavelengths (350–700 nm, with IPCE values of 80%, surpassing those of benchmark dye YD2-oC8) and remarkable PCEs (Figure 11H) (Pellejà et al, 2014; Li et al, 2016). The indoline motifs show nonplanar geometry enabling to endow the dye molecules with a proper steric hindrance to reduce the molecular aggregation.…”
Section: A4 β-Pyrrolic Substituted Znii Porphyrins As Light Harvestersmentioning
confidence: 99%
“…Finally, indoline-conjugated units have been considered, producing DSSCs with improved photocollection over a wide range of wavelengths (350–700 nm, with IPCE values of 80%, surpassing those of benchmark dye YD2-oC8) and remarkable PCEs (Figure 11H) (Pellejà et al, 2014; Li et al, 2016). The indoline motifs show nonplanar geometry enabling to endow the dye molecules with a proper steric hindrance to reduce the molecular aggregation.…”
Section: A4 β-Pyrrolic Substituted Znii Porphyrins As Light Harvestersmentioning
confidence: 99%
“…It was previously reported that continuous light exposure provides a way to signicantly and irreversibly improve solar cell efficiency. 34 TiO 2 works as a photobleaching catalyst, which promotes photocatalytic oxidation of the dye. 35 According to the literature, it is likely, that there is a weak interaction between the nitro group and the TiO 2 surface when d and d 0 are adsorbed via the carboxylate group.…”
Section: Nitro Effectmentioning
confidence: 99%
“…Recently, researchers started to put some eggs to the other bucket (Yang et al, 2014 ; Qi et al, 2018 ). For example, some electron-donating groups in organic sensitizer were successfully applied in porphyrin, such as N-annulated perylene ( 26 in Figure 4 ) (Jiao et al, 2011 ; Luo et al, 2013 , 2016 ), 2-diphenylaminothiophene ( 23 in Figure 4 ) (Wang et al, 2014d ), indoline ( 24 in Figure 4 ) (Pellej et al, 2014 ), phenothiazine ( 31 in Figure 4 ) (Xie et al, 2015 ), and even ferrocene (van der Salm et al, 2015 ). Some concepts from low-band-gap polymer were successfully applied in adjusting the absorption area and energy alignment of the porphyrins, such as weak donor-strong acceptor (Zhou et al, 2012 ; Bai et al, 2018 ; Lin et al, 2018 ; Xie et al, 2018 ), which will be discussed in the following part.…”
Section: The Development Of Porphyrins For Solar Cell Applicationmentioning
confidence: 99%